Rhizosphere-dwelling halophilic archaea: a potential candidate for alleviating salinity-associated stress in agriculture - Naitam, Mayur G.; Ramakrishnan, B.; Grover, Monendra; Kaushik, Rajeev (Frontiers in Microbiology, 2023)
Salinity is a serious environmental factor that impedes crop growth and drastically reduces yield. This study aimed to investigate the potential of halophilic archaea isolated from the Rann of Kutch to alleviate the negative impact of salinity on crop growth and yield. The halophilic archaea, which demonstrated high tolerance to salinity levels up to 4.5 M, were evaluated for their ability to promote plant growth in both salt-tolerant and salt-susceptible wheat cultivars. Our assessment focused on their capacity to solubilize essential nutrients, including phosphorus (14-61 mg L-1), potassium (37-78 mg L-1), and zinc (8-17 mg L-1), as well as their production of the phytohormone IAA (17.30 to 49.3 μg mL-1). To conduct the experiments, five wheat cultivars (two salt-tolerant and three salt-susceptible) were grown in triplicates using soft MS agar tubes (50 mL) and pots containing 10 kg of soil with an electrical conductivity (EC) of 8 dSm-1. Data were collected at specific time points: 21 days after sowing (DAS) for the MS agar experiment, 45 DAS for the pot experiment, and at the time of harvest. In the presence of haloarchaea, the inoculated treatments exhibited significant increases in total protein (46%), sugar (27%), and chlorophyll (31%) levels compared to the uninoculated control. Furthermore, the inoculation led to elevated accumulation of osmolyte proline (31.51%) and total carbohydrates (27.85%), while substantially reducing the activity of antioxidant enzymes such as SOD, catalase, and peroxidase by 57-76%, respectively. Notably, the inoculated treatments also showed improved plant vegetative growth parameters compared to the uninoculated treatments. Interestingly, the positive effects of the halophilic archaea were more pronounced in the susceptible wheat cultivars than in the tolerant cultivars. These findings highlight the growth-promoting abilities of the halophilic archaeon Halolamina pelagica CDK2 and its potential to mitigate the detrimental effects of salinity. Consequently, further evaluation of this halophilic archaeon under field conditions is warranted to explore its potential use in the development of microbial inoculants.